Detection of individual differences in radiation-induced apoptosis of peripheral blood lymphocytes in normal individuals, ataxia telangiectasia homozygotes and heterozygotes, and breast cancer patients after radiotherapy. - Barber, J; West, C; Kiltie, A; Roberts, SA; Scott, D (2000)
Quantification of radiation-induced apoptosis in peripheral blood lymphocytes (PBLs) has been proposed as a possible screening test for cancer-prone individuals and also for the prediction of normal tissue responses after radiotherapy. We have used the TUNEL assay (terminal transferase nick-end labeling) 24 h after irradiation with 4 Gy at high dose rate to assess interindividual differences in radiation-induced apoptosis between (1) a panel of normal individuals, (2) ataxia telangiectasia (AT) homozygotes and heterozygotes, and (3) breast cancer patients who had received radiotherapy 8-13 years ago, including a number of patients who had suffered adverse responses to radiation. With this protocol, we show clear differences in radiation-induced apoptosis between individuals, and good reproducibility in the assay. In agreement with previous reports using EBV-transformed lymphoblasts, we show a very poor induction of apoptosis in AT homozygotes and a reduced level in AT heterozygotes compared to normal individuals. A similar reduced level compared to normal individuals was seen in the breast cancer patients. Despite a wide range of values in the breast cancer patients and good reproducibility on repeat samples, there was no correlation of rates of apoptosis with the severity of breast fibrosis, retraction or telangiectasia. The reduced rate of apoptosis observed in the breast cancer cases may be associated with genetic predisposition to breast cancer; however, we conclude that assays of lymphocyte apoptosis are unlikely to be of use in predicting normal tissue tolerance to radiotherapy.